MANAJEMEN PENGEMBANGAN SUMBER DAYA MUTU GURU DI MTs NEGERI TRIWARNO KUTOWINANGUN KEBUMEN - Isnaini, Isnaini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to find and examine more deeply about a clear picture of resource development management related quality of teachers at MTs Kutowinangun Kebumen. Main issues discussed were: (1) How resource development quality of teachers at MTs Kutowinangun? (2) How to organize the development of quality resource teacher at MTs Kutowinangun? (3) How is the implementation of resource development the quality of teachers at MTs Kutowinangun? (4) How does the evaluation and maintenance of quality of teachers resource development at MTs Kutowinangun. This type of research in this thesis is a case study with qualitative descriptive explorative, ie research aimed at describing the situation or phenomenon, with the view of education as a source of immediate environment, its results in the form of words. Data collection techniques using observation, interviews and documentaries. Analysys data analysis techniques using Interactive, with data collection, data reduction, data presentation and conclusion / verification. From the research that I did obtained the following conclusions: the development of quality management functions of teachers in MTs N Kutowinangun Kebumen which include planning, organizing, implementation and assessment. Of these four functions are already well underway. After the implementation of quality management development resource teacher at MTs Kutowinangun Kebumen can already be regarded as qualified teachers in accordance with the desired objectives.